Transfer of a yeast artificial chromosome carrying human DNA from Saccharomyces cerevisiae into mammalian cells. - Pachnis, V (1990)
To test the feasibility of transferring yeast artificial chromosomes (YACs) into mammalian cells, we modified a YAC that carries approximately 450 kilobases (kb) of human DNA, by inserting a neomycin-resistance gene. Saccharomyces cerevisiae cells carrying this YAC were fused by polyethylene glycol to mouse L cells and G418-resistant colonies were obtained. A high percentage of these clones contained virtually intact YAC sequences as revealed by "Alu fingerprint" analysis and restriction enzyme analysis using pulsed-field gel electrophoresis. Furthermore, the YAC sequences were stably integrated into the mouse chromosomes, as shown by in situ hybridization and by the stability of the G418 resistance. These results establish that large segments of the mammalian genome, cloned in yeast, can be efficiently transferred into cultured mammalian cells.